2020
DOI: 10.1177/0971890720914121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Determinants of Online Customer Experience on Online Customer Satisfaction

Abstract: The role of online retailing is increasing with each passing day for any business and therefore offering value to the customer which in turn also yield benefit to the retailer and differentiate it from the competitors is an important task. By getting an idea of how customer perceive and evaluate the offerings, retailers may be able to influence the customers in that particular direction. This research paper aims in identifying the major factors or attributes that affect the customers, evaluating their overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 47 publications
6
38
3
1
Order By: Relevance
“…Many studies have focused on the factors affecting the customer experience (antecedents), as well as the impact of customer experience (consequences) on key marketing concepts such as satisfaction and loyalty (Garepasha et al , 2020; Shin, 2015; Yazdanparast and Tran, 2020). A review of the literature shows that many studies have investigated customers’ experience into both offline and online platforms (Bilgihan, 2016; Bilgihan et al , 2016; Bleier et al , 2018; Brun et al , 2017; García et al , 2018; Garepasha et al , 2020; Jaiswal and Singh, 2020; Johnston et al , 1999; McLean, 2017; McLean and Wilson, 2016; Rose et al , 2012; Rose et al , 2011; SeungHyun et al , 2011; Verhoef et al , 2009; Waqas et al , 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Many studies have focused on the factors affecting the customer experience (antecedents), as well as the impact of customer experience (consequences) on key marketing concepts such as satisfaction and loyalty (Garepasha et al , 2020; Shin, 2015; Yazdanparast and Tran, 2020). A review of the literature shows that many studies have investigated customers’ experience into both offline and online platforms (Bilgihan, 2016; Bilgihan et al , 2016; Bleier et al , 2018; Brun et al , 2017; García et al , 2018; Garepasha et al , 2020; Jaiswal and Singh, 2020; Johnston et al , 1999; McLean, 2017; McLean and Wilson, 2016; Rose et al , 2012; Rose et al , 2011; SeungHyun et al , 2011; Verhoef et al , 2009; Waqas et al , 2020).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Customers who have a positive shopping experience at a retailer have a higher likelihood of being involved in spreading positive word of mouth recommendations and reusing services [2]. Determining factors that affect the customer experience of shopping online important in exploration with the aim of understanding its impact on customer satisfaction on digital platforms [3].…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, shopping experiences are more related to consumers' perceptions, feelings, emotions and sensations towards the usage of online shopping. The previous study found that the source economic value, customization, customer service, and post-purchase experience are the most outstanding catalysts of online customer experience (Jaiswal & Singh, 2020).…”
Section: Experiencesmentioning
confidence: 98%